Innocenti social monitor 2006 : understanding child poverty in So uth-Eastern Europe and the Commonwealth of Independent States - UNICEF. Innocenti Research Centre (Florence, Italy: UNICEF Innocenti Research Centre, 2006)
"This is a study of child poverty in a fast-changing region ... Purs uing a child rights perspective, the study sets out to measure and unde rstand better the nature and scale of child poverty, as distinct from a dult poverty; it highlights the large disparities in child well-being w hich have emerged in this period of economic expansion, between countri es, between regions in countries, and between families; it points to a way in which governments in the region could more effectively address m arginalisation and disparities among children." - back cover.
Includes bibliographical references (p. 93-96, 123)
Keywords: Poor children -- Former Soviet republics; Poor children -- Balkan Peninsula; Child welfare -- Balkan Peninsula -- Social conditions; Child welfare -- Former Soviet republics -- Social conditions